Quantitative assessment of platelet-rich plasma in enhancing bone regeneration and healing in osteoporotic fractures - Hussein, Wisam A.; Alkhatteib, Hussain J.; Naeem, Sarah Mazin (International Journal of Innovative Research and Scientific Studies, 2025)
Osteoporotic fractures pose a significant clinical challenge due to impaired bone healing and an increased risk of nonunion. Platelet-rich plasma (PRP) has emerged as a promising therapeutic intervention due to its high concentration of bioactive molecules that stimulate bone regeneration. This randomized controlled trial aimed to evaluate the efficacy of PRP in enhancing fracture healing in elderly patients with osteoporosis. Fifty patients diagnosed with osteoporotic fractures were randomly assigned to either the PRP group (n=25), receiving a single injection of PRP at the fracture site, or the standard guideline therapy group (n=25), receiving the usual standard treatment for such fractures. Fracture healing outcomes were assessed over six months through radiographic imaging, bone mineral density (BMD) measurement, pain assessment using the Visual Analog Scale (VAS), and functional recovery evaluated by the Timed Up and Go (TUG) test. Additionally, serum biomarkers of bone formation, including osteocalcin and alkaline phosphatase, were analyzed. The results demonstrated that the PRP group exhibited significantly higher radiographic union scores (7.8 ± 1.1 vs. 5.8 ± 1.7, p = 0.0001), greater improvement in BMD (3.3 ± 1.9% vs. 1.8 ± 2.9%, p = 0.02), lower VAS scores (2.4 ± 1.8 vs. 4.1 ± 2.1, p = 0.001), and shorter TUG test completion times (14.5 ± 3.1s vs. 18.6 ± 3.5s, p = 0.0001) compared to the standard guideline therapy group. Biochemical analysis revealed significantly elevated osteocalcin (33.5 ± 7.3 ng/mL vs. 23.9 ± 5.5 ng/mL, p = 0.0001) and alkaline phosphatase levels (119.4 ± 23.1 U/L vs. 102.3 ± 20.4 U/L, p = 0.01) in the PRP group, suggesting enhanced osteoblastic activity. These findings indicate that PRP significantly improves fracture healing, enhances bone regeneration, reduces pain, and accelerates functional recovery in osteoporotic patients. Further research is needed to optimize PRP protocols and establish long-term efficacy in clinical applications.